Reading Victorian literature : essays in honour of J. Hillis Miller - Wolfreys, Julian, 1958-; Szuba, Monika; Miller, J. Hillis (Joseph Hillis), 1928-2021 (Edinburgh University Press, 2019)
Reading Victorian Literature provides a critical commentary on major authors of the nineteenth and early twentieth centuries, from Dickens to Conrad. At the same time, the assembled group of internationally recognised scholars engages with Miller's work, influence and significance in the study of that era. The volume includes original work by Miller and interviews with him.
Keywords: English literature -- 19th century -- History and criticism.; English literature -- 20th century -- History and criticism.; Littérature anglaise -- 19e siècle -- Histoire et critique.; Littérature anglaise -- 20e siècle -- Histoire et critique.; English literature; Englisch; Literatur; Großbritannien; 1800-1999; Criticism, interpretation, etc.